Analysis of metabolites from plants of the Swartzia genus using chemical indexes: evolutionary tendencies - Magalhães, Aderbal Farias; Tozzi, Ana Maria Goulart de Azevedo; Santos, Celira Caparica; Magalhães, Eva Gonçalves (Eclética Química, 2006)
The chemical indexes, suggested by Gottlieb et al., have not been used before regarding evolutionary tendency of species in the Swartzia genus. However, the importance of this work encour- aged for an analysis of the Swartzia genus using the metabolites isolated from nine species. The analy- sis, based on calculated chemical indexes, provided an evolutionary tendency for these plants, which correlates with the classification based on morphological analysis.